2021
DOI: 10.1016/j.redox.2021.102104
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic dysregulation in bronchopulmonary dysplasia: Implications for identification of biomarkers and therapeutic approaches

Abstract: Bronchopulmonary dysplasia (BPD) is a common chronic lung disease in premature infants. Accumulating evidence shows that dysregulated metabolism of glucose, lipids and amino acids are observed in premature infants. Animal and cell studies demonstrate that abnormal metabolism of these substrates results in apoptosis, inflammation, reduced migration, abnormal proliferation or senescence in response to hyperoxic exposure, and that rectifying metabolic dysfunction attenuates neonatal hyperoxia-induced alveolar sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 160 publications
(207 reference statements)
0
4
0
Order By: Relevance
“…BPD is a chronic lung disease affecting the life and health of preterm infants [ 32 ]. Previous studies have demonstrated an association of BPD with adverse respiratory outcomes and neurodevelopmental dysfunctions in children [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…BPD is a chronic lung disease affecting the life and health of preterm infants [ 32 ]. Previous studies have demonstrated an association of BPD with adverse respiratory outcomes and neurodevelopmental dysfunctions in children [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…BPD is a chronic lung disease initiated by inflammation and oxidative stress during the canalicular and saccular stages of lung development, disrupting alveolar and vascular growth ( Thébaud et al, 2019 ). Mitochondrial dysfunction, impaired oxidative phosphorylation, and their downstream effects are all operative in BPD pathogenesis ( Ratner et al, 2009 ; Yue and Yao, 2016 ; Kandasamy et al, 2017 ; Shah et al, 2018 ; Xuefei et al, 2021 ; Yue et al, 2021 ). Mitochondrial density continues to increase during the postnatal period to support normal lung development and growth but mitochondrial density and function are disrupted in infants with BPD ( El-Merhie et al, 2017 ).…”
Section: Mitochondrial Dysfunction In Preterm Infants and Its Downstr...mentioning
confidence: 99%
“…The diagnosis, as per existing criteria, can only be established at the corrected age of 36 weeks, and the lack of specific treatment modalities underscores the imperative need for sensitive early biomarkers for BPD [ 3 ]. Metabolomics assays have evidenced altered glucose, lipid, and amino acid metabolism in preterm infants who develop BPD, suggesting that dysregulated glucose metabolism may serve as a predictive marker for BPD onset in preterm neonates [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%